PROPERTIES OF ESTRUAL CERVICAL MUCUS IN RELATION TO PLASMA PROGESTERONE AND CONCEPTION RATES IN BUFFALOES - SHRMA, H C; DHAMI, A J; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
The examination of estrual cervical mucus samples from 61 normal cyclic buffaloes at Al revealed clear thinwatery, stringy and turbid consistency in 42.62, 37. 71 and 19.67 % cases. Typical, atypical and nil fern pattern ofmucus was observed in 39.34, 42.63 and 18.03 % samples, respectively. Maximum number of buffaloes (60.86 %)conceived when they had clear stringy mucus with mean plasma P 4 of0.26 ± 0.04 ng/ml, followed by those (15.38%) with clear thin watery mucus with P 4 of 0.54 ± 0.1 Ong/ml and those with typical and atypical fern pattern (45.83and 26.92 %). The spinnbarkeitvalue of mucus averaged 9.35 ± 0.66 cm. It was significantly higher (P < 0.01) inconceived than non-conceived buffaloes (12.94 ± 0.81 vs 7.91 ± 0.96 cm) with inverse plasma P4 (0.21 ± 0.04 vs0.56 ± 0.11 ng/ml). The mean spinnbarkeit value of thick stringy mucus was significantly higher (P < 0.01) withlower plasma P 4 than the other two grades. With regards to association, maximum animals conceived when theyhad both thick stringy mucus with typical fern pattern (44.44 %) followed by thick mucus with atypical fern pattern(33.33 %) and thin watery mucus with typical and atypical fern pattern (16.66 and 5.55 %). The overall first serviceconception rate in this study was 29.50 %. The findings clearly showed that for better conception rates in buffaloes,Al should be done when there is clear stringy mucus with higher spinnbarkeit and typical fern pattern associatedwith basal plasma progesterone levels.
Keywords: Normal cyclic buffaloes; Cervical mucus; Physical properties; Conception rate